(3QSGdI aj NWC ef bGd LhgQjIs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPi NU GdEfSGf HTQa GdNWGH CeG HYO deG EdJeSJ CjgG GdGN GdTajb hGdYGbd GdUOjb Cf CcJH QSGdI ai GdUdGI hGTQM MbjbJgG GdeJYdbI Zdi XGgQgG GdeCehQ hEdi HGWfgG GdeWdhH s
(3BNQgG (B:s
(3hGQOfG Cf fTQM dcd YHGOI NGUI hdcf JYPQ YdjfG GdTQhY ai CehQ dGjUdM GdEWdGY YdjgG dCMO hGdMeO ddg cdg dhGgH Gdcd hGddg GYde JeJ JeGe s
(3GdejcQhajde ZjQ ehLhO GfXQ QSGdI EjVGM HQGgjf Qbe (B34s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
(3NOGHNT HJfg (B(898) s
Keywords: (3GdadSaI hGdefWbs